Testing The Scientificity of Progressive Legal Theory Through Karl Popper's Falsification: A Study of the Philosophy of Science - Samosir, Daniel; Hadinata, Fristian (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The development of scientific knowledgestarting from a problem that often arises because the existing theory is seen as unable to solve or is no longer adequate to overcome the problem. The progressive legal theory initiated by Satjipto Rahardjo was born when the existing legal theory was seen as no longer adequate to overcome legal problems in Indonesian society. However, the problem with the progressive legal theory that has not been seriously touched on so far is the scientific nature of the progressive legal theory as a theory from the perspective of the philosophy of science. According to Popper, a theory is scientific if and only if it can be refuted by an event that can be imagined. Falsification for Popper is a demarcation criterion that provides a distinction between scientific and non-scientific theories or pseudoscience. Therefore, it is important to conduct research on whether the progressive legal theory is a scientific, non-scientific, or pseudoscience theory? so that the progressive legal theory undergoes corroboration (confirmation). This study uses a library research method with a qualitative approach, using a descriptive method (descriptive-analytical). The results of this study are based on the application of falsification to the progressive legal theory, which has a theoretical corein the form of a hypothesis“law is not just a matter of rule, but also of behavior”, isNofalsifiable, thus non-scientific. However, this does not mean that progressive legal theory is not enlightening or meaningless.